Pengaruh Komunikasi Interpersonal Terhadap Kinerja Karyawan PT. Taurina Travel Djaya - Ahmad Rif’at; Fa’uzobihi; Kaffah Imanuddin MR Santosa (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The goals of each organization are different from each other, for example there are profit-oriented organizations and non-profit-oriented organizations. Profit-oriented organizations are hereinafter referred to as companies. The phenomenon that occurs regarding Employee Performance at PT. Taurina Travel Djaya, Jakarta branch is a decline in consumers in the last year. The number of customers using travel services tends to decrease, although there are several other factors such as Covid-19 which has completely stopped the travel sector. Employee Performance Assessment is obtained from the results of performance evaluations with several Items that must be assessed with their respective weights. The following is a table of Evaluation Items used at PT. Taurina Travel Djaya. Based on this theory, quantitative descriptive research, is data obtained from a sample of the research population analyzed according to the statistical methods used. The population and sample in this study were 30 employees working at PT Taurina Travel Djaya. research results The results of the study stated that there are many factors that influence employee interpersonal communication at PT. Taurina Travel Djaya, Jakarta branch. These factors are mainly influenced by the comfort of communication, the level of familiarity and approach. This shows that good interpersonal communication in a work environment will improve the quality and comfort of the work environment. that interpersonal communication is positively correlated with employee performance. The better interpersonal communication in the work environment, the better employee performance in the context of work results, job knowledge, initiative, mental agility and attitude in completing work and Based on simple regression analysis, Interpersonal Communication has a significant effect on employee performance. With a regression coefficient of 0.169 and a significance value of 0.017 (below 0.05), the study shows that interpersonal communication can improve employee performance.